Beza, Guide for the Faithful Life - Raitt, Jill (Scottish journal of theology, 1986)
To date, work on Theodore Beza has dealt with his life, his theology, his biblical works, some aspects of his political activity and treatises, and his contribution to literature. Beza as a pastor, as a shepherd of souls concerned for their growth in Christ, has not yet received attention. But it is through such a study that Beza's character becomes known to us. Beza was not merely a skilled diplomatist, an excellent poet, and a devoted professor of the Genevan Academy. As a theologian he defended Calvin's doctrine, developing it as he thought necessary in response to attack or because of a profound insight into the nature of word and sacrament. But at the root of these activities was Beza's own life of faith nourished by Scripture and the Lord's Supper and shared with his flock and his students through a drama, commentaries and sermons, two manuals of prayer, and letters of spiritual advice or consolation.